2020
DOI: 10.1155/2020/4749712
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Wound Healing Property of Jacaranda decurrens Cham. (Bignoniaceae): An Experimental Study Based on Molecular Mechanisms

Abstract: Background. Jacaranda decurrens Cham., known as carobinha, is prevalent in the Cerrado biome and presents popular use in treatment of dermatological diseases. The present study aimed to investigate the healing action of topical formulation of Jacaranda decurrens Cham. (FtEHJ) in mice cutaneous lesions. Methods. Phytochemical analysis of J. decurrens hydroalcoholic extract was carried out by using HPLC-PDA-ESI-MS and FIA-ESI-IT-MSn. Swiss mice were treated topically with formulation base (FtB) or Fibrinase® or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
4
0
1
Order By: Relevance
“…Regarding Jacaranda decurrens Cham., metabolic profiling was done to find out ten compounds in the extract of flavonoidal and triterpenoidal nature. It was concluded that these compounds improved the healing of wounds in this study (Serra et al 2020). Hydroethanolic extract of leaves of Lafoensia pacari A. St.-Hil.…”
Section: Wound Healing Potentials Of Various Plant Extractssupporting
confidence: 50%
“…Regarding Jacaranda decurrens Cham., metabolic profiling was done to find out ten compounds in the extract of flavonoidal and triterpenoidal nature. It was concluded that these compounds improved the healing of wounds in this study (Serra et al 2020). Hydroethanolic extract of leaves of Lafoensia pacari A. St.-Hil.…”
Section: Wound Healing Potentials Of Various Plant Extractssupporting
confidence: 50%
“…The samples were then filtered using a 0.22-µm PTFE filter and dried. The extract was diluted to 10 µg/mL in the HPLC solvent, and then, aliquots of 20 µL were injected directly into the LC-ESI-IT/MS [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sample was injected into the HPLC system, where it was analyzed online by ESI-MS in the negative ion mode with a UV detector. Mass spectrometry was performed in an LCQ Fleet Ion Trap LC/MSⁿ—Thermo Scientific ® (Waltham, MA, EUA) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Espécies de Tecoma, em estudos in vitro, evidenciaram atividade contra o Zika vírus (Reis et al, Research, Society and Development, v. 11, n. 2, e5611222891, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i2.22891 3 2020). A Jacaranda decurrens Cham exibiu atividade cicatrizante de feridas cutâneas (Serra et al, 2020). Enquanto a Cecropia pachystachya apresentou atividade antibacteriana a partir de extratos aquosos e etanólicos contra cepas de Staphylococcus aureus (Costa & Hoscheid, 2018).…”
Section: Introductionunclassified